Pengaruh Kepemilikan Manajerial Terhadap Kesulitan Keuangan Perusahaan Sektor Industri Dasar Dan Kimia - Firdaus, Dhoni; Anshari, Rahman; Jamal, Sri Wahyuni (Value : Jurnal Manajemen dan Akuntansi, 2024)
Managerial ownership is believed to reduce agency problems that frequently occur in business, which, if not addressed, can lead to financial distress for the company. Extremely high or low managerial ownership can cause issues, such as managers neglecting shareholders' interests or being less motivated to maintain the company's financial stability. This study aims to analyze the effect of managerial ownership on the likelihood of financial distress in basic industry and chemical sector companies listed on the Indonesia Stock Exchange (IDX). A quantitative approach was used in this study. The data consists of annual reports from basic industry and chemical sector companies listed on the IDX from 2018 to 2023. Samples were determined using a purposive sampling method from a population of 73 companies, resulting in 24 companies with a total of 144 samples analyzed. Logistic regression analysis was used to test the hypothesis. The results of this study indicate that higher managerial ownership is associated with a reduced likelihood of financial distress. The findings of this study are useful for shareholders and management in making decisions regarding ownership structure to minimize financial risk.